Cultural psychology and children's understanding of institutional reality / La psicología cultural y la comprensión de los niños de la realidad institucional. Issue 1 (2nd January 2019) - Moreno, Fernando A.; Packer, Martin J.
Abstract: This article will describe and illustrate an approach to empirical investigation that is grounded in a basic principle of cultural psychology: that culture is a constituent of human psychological functioning. Cultural artefacts provide the means by which people interact with the world around them and with other people. Humans live in artificial environments, and in a real sense humans too are artificial. Specifically, humans live in societies composed of institutions, such as family, school, workplace, and children must become able to assume roles in these institutions. To investigate children's development, which is our interest, it is necessary not merely to study children in their cultural context, but also to design and implement changes in that cultural context. Untangling the complex, changing relationship between child and cultural context is greatly facilitated by actively transforming this institutional reality, in interaction with the children. We illustrate this point with descriptions of a project, five years in duration, in Ciudad Bolívar, Colombia, in which we established a small institution, a Fifth Dimension, in which children participated in playful and educational activities.